MERANCANG KASIH SAYANG MENJADI PENGALAMAN PENGEMBANGAN MEDIA INTERACTIVE POP-UP BOOK "AKU SAYANG TEMAN" UNTUK ANAK USIA DINI - Muchtar, Rembulan Hawnan Wafi; Christiani Endah Poerwati; Ni Komang Theda Febrina Subagia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The early years of a child's life are a window of opportunity that opens only once. Between the ages of 0 and 6, children do not merely grow they construct the very foundation of their social lives. Yet, the reality observed in early childhood classrooms suggests that meaningful opportunities for children to learn love and empathy are increasingly displaced by digital screens. This study responds to that concern by asking: how might we design a medium that transforms the value of compassion into an experience that children can touch, feel, and make their own? Using a 4D developmental research model (Define, Design, Develop, Disseminate), this study produced an Interactive Pop-Up Book titled "Aku Sayang Teman" (I Love My Friends) a three-dimensional book with 13 pages of interactive activities deliberately crafted to nurture affection, empathy, and care for peers across all differences. The media's feasibility was assessed by two content experts, two media experts, and two early childhood practitioners using a 1 - 5 rating scale instrument. Findings reveal a content validity score of 90%, media validity of 90%, and practitioner practicality rating of 95% all classified as Excellent. The media is declared ready for classroom implementation as a tangible alternative for character education in early childhood institutions.